Cooperation amidst competition: cybersecurity partnership in the US financial services sector. Issue 1 (2nd December 2021) - Atkins, Sean; Lawson, Chappell
ABSTRACT: The US Financial Services Sector (FSS) is commonly regarded as one of the most successful in addressing cybersecurity through public–private partnership and as a potential model for less advanced sectors. However, how well the sector has actually fared remains poorly understood. Based on publicly available material and in-depth interviews with those intimately involved in business–government collaboration on cybersecurity in the FSS, we analyze how and why collaboration evolved into its current form. We find that considerable gaps remain, which both reveal limitations in the current policy framework for the FSS and suggest lessons for other critical infrastructure sectors.